Species composition and distributional characteristics of Panulirus White, 1847 (Palinuridae) in Cu Lao Cham marine protected area, Quang Nam province - Tho, Le Van; Thao, Le Ngoc; Dang, Phan Doan; Dien, Huynh Ngoc; Dat, Hoang Duc (Academia Journal of Biology, 2014)
Among total 22 specimens of spiny lobster collected from two fieldtrips in the Cu Lao Cham marine protected area (MPA), Quang Nam province on May and November 2012, we have identified six species belong to genus Panulirus: Panulirus longipes, P. stimpsoni, P. versicolor, P. ornatus, P. penicillatus and P. homarus. At present, the species of genus Panulirus have recorded for Cu Lao Cham MPA estimates 75.0% of spiny lobster species reported for Vietnam. Five of which are listed in the 2007 Red Data Book of Vietnam as Endangered (Panulirus longipes), Vulnerable (P. ornatus, P. versicolor and P. homarus) and Data Deficient (P. stimpsoni and P. penicillatus). The Panulirus species popularly found in the Cu Lao Cham MPA, most of dominant areas are Hon Lao, Hon Mo, Hon Dai and Hon La island. Spiny lobsters of Cu Lao Cham MPA were found at different habitats, the sites may with mud, sand and gravel, coral reefs, caves, or rocks at a depth from 0.5 to 30 meters. Annually, they were frequently recorded from March to July and rarely seen in the remaining time of the year. This time is also the breeding season of most spiny lobster species in Cu Lao Cham MPA.